2008
DOI: 10.1063/1.2975155
|View full text |Cite
|
Sign up to set email alerts
|

Negative refraction at the pure Ag/air interface observed in the visible Drude region

Abstract: Pure negative refraction was found for a series of prismlike Ag film samples measured in the visible Drude region. Results show that the pseudonegative refraction index nm changes with the photon energy and has a spectral trend to be less negative with the increasing energy. Light refraction will be expected to be positive in the higher energy region where the interband transitions dominate the interaction between the electrons and photons in Ag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The results presented in this work further support the suggestion that the fundamental optical properties of light transmission at the pure metal/dielectric interface will play a key role in understanding either positive or negative refraction in the metal-based metamaterials. Of the noble metals, Ag has a purely ''free'' electron response to produce the widest negative refraction region in the visible region, 21) while Cu's negative visible refraction region is the narrowest in the lower energy region. The results of this work can be used to explain and predict that by mixing a noble metal which has a fundamentally negative refraction in a certain wavelength region with a material which has a positive refraction at a usual interface, or by adding some microstructures, light refraction of a noble-metal-based metamaterial may change profoundly with wavelength under different physical conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented in this work further support the suggestion that the fundamental optical properties of light transmission at the pure metal/dielectric interface will play a key role in understanding either positive or negative refraction in the metal-based metamaterials. Of the noble metals, Ag has a purely ''free'' electron response to produce the widest negative refraction region in the visible region, 21) while Cu's negative visible refraction region is the narrowest in the lower energy region. The results of this work can be used to explain and predict that by mixing a noble metal which has a fundamentally negative refraction in a certain wavelength region with a material which has a positive refraction at a usual interface, or by adding some microstructures, light refraction of a noble-metal-based metamaterial may change profoundly with wavelength under different physical conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we have shown that both positive and negative refraction can be observed at the pure Au/air and Ag/air interfaces in the visible region by avoiding most of the side effects from microstructures. 20,21) Note that in the Drude region ''free'' electrons determine the dielectric function, which has a negative real part, and in the interband region the real part and the optical response are determined by ''bound'' electrons. In the present work, we have studied the third noble metal, Cu, which is one of the few materials having a fairly clean separation of the two regions of intraband and interband transitions in the visible region that is in an easily accessible region of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The working pressure, discharge voltage, current, and power were fixed at 3.0 9 10 -3 mbar, 410 V, 0.17 A, 70 W, respectively. A mask was driven at a constant velocity of about 11.4 lm/s by a stepping motor during the deposition process to obtain the wedge-shaped sample [29,30].…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, a wedge-shaped sample [29,30] was deposited under the identical conditions by magnetron sputtering on K9 glass. The surface contamination, oxidation, roughness, and interfacial layer are the same, which can effectively exclude the influence from these factors on the intrinsic values of dielectric functions [19,24,31,32] of Ti thin film due to different samples.…”
Section: Introductionmentioning
confidence: 99%
“…from metal to dielectric. [8][9][10] Other generalized versions of the Snell's laws are based on complex or real valued boundary conditions, and quite different results are obtained. [11][12][13][14][15] Moreover, the experimental verification is extremely difficult because the associated heavy absorption results in opacity and a very short penetration depth.…”
Section: Introductionmentioning
confidence: 99%